2002
DOI: 10.1079/bjn2002613
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of different types of folate in healthy subjects with an ileostomy

Abstract: Our knowledge on the absorption of folate is incomplete. The deconjugation process as a possible limiting factor in the absorption of folates was investigated. The study also attempted to validate the use of the area under the serum response curve (AUC) from food compared with folic acid as a proxy variable for food folate bioavailability. Folate absorption was determined in healthy ileostomy volunteers (n 11) using a single-dose short-term protocol. In a randomised crossover design, volunteers received spinac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…Relative folate absorption was estimated by plasma AUCs after ingestion of a test food versus a reference dose. In contrast to other studies, in which an oral dose of a folic acid pharmaceutical was given as a reference dose (11,18), the biological form (6S)-5-CH 3 -H 4 folate, which is given by intramuscular injection, was chosen. Volunteers' body stores were standardized by saturation before each test day to minimize the hepatic first-pass uptake affecting the plasma response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative folate absorption was estimated by plasma AUCs after ingestion of a test food versus a reference dose. In contrast to other studies, in which an oral dose of a folic acid pharmaceutical was given as a reference dose (11,18), the biological form (6S)-5-CH 3 -H 4 folate, which is given by intramuscular injection, was chosen. Volunteers' body stores were standardized by saturation before each test day to minimize the hepatic first-pass uptake affecting the plasma response.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only one folate ileostomy trial has been published (18), indicating a high folate absorption between 73 and 91% from two spinach meals and an oral dose of folic acid based on 24 h postdose stomal folate excretion. Volunteers showed a remarkably high interindividual variation, as expressed by CVs of 60Á/90% (n0/11) for individual ileostomal folate excretion on the same test days.…”
Section: Food Folate Bioavailabilitymentioning
confidence: 99%
“…below the 85 % bioavailability used previously for vehicles (Finglas et al 2002b). Another recent study has also found much higher absorption of spinach folate (79 %) relative to a folic acid supplement, using an ilesotomy model in which the difference between folate intake and the folate content of ileostomy effluents was used to calculate absolute absorption (Konings et al 2002).…”
Section: Absorption and Metabolismmentioning
confidence: 99%
“…Twelve food items were studied, of which banana and lima beans (Phaseolus limensis) were found to contain highlybioavailable folates (82-96% relative to FA), whereas folates from other foods such as romaine lettuce, orange juice, cabbage, soybean meal and wheat germ have a low bioavailability (25-47 %). More-recent studies, based on the determination of serum folate area under the curve, have reported that the bioavailability of folates from wheataleurone flour (Fenech et al 1999) and from spinach (Konings et al 2002) is similar to that of an equivalent amount FA provided as a tablet. The reported differences between studies in the bioavailability of folates from various foods are probably the result of differences in the protocols used, together with any inherent differences between the foods administered, including the food matrices and other potential factors affecting folate bioavailability (GCPII inhibitors, pH).…”
Section: Acute Studiesmentioning
confidence: 99%